Biomaterials for vascular tissue engineering - Ravi, Swathi (2010)
Cardiovascular disease is the leading cause of mortality in the USA. The limited availability of healthy autologous vessels for bypass grafting procedures has led to the fabrication of prosthetic vascular conduits. While synthetic polymers have been extensively studied as substitutes in vascular engineering, they fall short of meeting the biological challenges at the blood–material interface. Various tissue engineering strategies have emerged to address these flaws and increase long-term patency of vascular grafts. Vascular cell seeding of scaffolds and the design of bioactive polymers for in situ arterial regeneration have yielded promising results. This article describes the advances made in biomaterials design to generate suitable materials that not only match the mechanical properties of native vasculature, but also promote cell growth, facilitate extracellular matrix production and inhibit thrombogenicity.